2016
DOI: 10.1186/s13068-016-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of long-chain acyl-CoA synthetases which stimulate secretion of fatty acids in green algae Chlamydomonas reinhardtii

Abstract: BackgroundMicroalgae biofuel has become the most promising renewable energy over the past few years. But limitations still exist because of its high cost. Although, efforts have been made in enhancement of lipid productivity, the major cost problem in harvesting and oil extraction is still intractable. Thus, the idea of fatty acids (FAs) secretion which can massively facilitate algae harvesting and oil extraction was investigated here.ResultsThe cDNAs of two long-chain acyl-CoA synthetases (LACSs) genes were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…However, there is no experimental evidence to determine the impact of NobZIP1 on the regulation of its key target genes, and hence, we carried out chromatin immunoprecipitation (ChIP) to investigate the regulatory role of NobZIP1 on the expression of other genes. ChIP analysis revealed that NobZIP1 regulates the expression of key genes involved in fatty acid, lipid, and carbohydrate metabolism, such as ACBP [acyl–coenzyme A (CoA)–binding protein] ( 24 ), KAS [3-ketoacyl-acyl carrier protein synthase] ( 25 ), LC-FACS (long-chain acyl-CoA synthetase) ( 26 ), LPAAT ( 26 ), and CPS (putative capsular polysaccharide synthesis gene) ( 11 ), and UGDH ( 27 ), the key genes involved in cell wall carbohydrate polymer metabolism (Fig. 3, A to F).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no experimental evidence to determine the impact of NobZIP1 on the regulation of its key target genes, and hence, we carried out chromatin immunoprecipitation (ChIP) to investigate the regulatory role of NobZIP1 on the expression of other genes. ChIP analysis revealed that NobZIP1 regulates the expression of key genes involved in fatty acid, lipid, and carbohydrate metabolism, such as ACBP [acyl–coenzyme A (CoA)–binding protein] ( 24 ), KAS [3-ketoacyl-acyl carrier protein synthase] ( 25 ), LC-FACS (long-chain acyl-CoA synthetase) ( 26 ), LPAAT ( 26 ), and CPS (putative capsular polysaccharide synthesis gene) ( 11 ), and UGDH ( 27 ), the key genes involved in cell wall carbohydrate polymer metabolism (Fig. 3, A to F).…”
Section: Resultsmentioning
confidence: 99%
“…LACS could be activated during both the synthesis of cellular lipids and their degradation through boxidation and also participates in the cutin pathway. [27][28][29] ACP is involved in the pathway for fatty acid synthesis and export. 30,31 FAH could catalyse the synthesis of hydroxylated fatty acid moieties, absence of which could increase the salicylate levels and resistance towards obligate biotrophic fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The irreversible depletion of fossil fuels and fossil fuel burning-associated global warming have accelerated the search for biofuel production via renewable feedstock over the past few years [1,2] . Due to some obvious advantages which include higher photosynthetic efficiency and biomass production rate, microalgal lipid, especially triacylglycerols (TAGs), have broadly been researched as a hidden biodiesel raw material [3] .…”
mentioning
confidence: 99%